Translating the ABC-02 trial into daily practice: outcome of palliative treatment in patients with unresectable biliary tract cancer treated with gemcitabine and cisplatin. (3rd June 2018) - Dierks, J.; Gaspersz, M. P.; Belkouz, A.; van Vugt, J. L. A.; Coelen, R. J. S.; de Groot, J. W. B.; ten Tije, A. J.; Meijer, W. G.; Pruijt, J. F. M.; van Voorthuizen, T.; van Spronsen, D. J.; Rentinck, M.; et al.
Abstract: Background: Biliary tract cancer (BTC) is an uncommon cancer with an unfavorable prognosis. Since 2010, the standard of care for patients with unresectable BTC is palliative treatment with gemcitabine plus cisplatin, based on the landmark phase III ABC-02 trial. This current study aims to evaluate the efficacy and safety of gemcitabine and cisplatin in patients with unresectable cholangiocarcinoma and gallbladder cancer in daily practice that meet the criteria for the ABC-02 trial in comparison to patients who did not. Methods: Patients diagnosed with unresectable BTC between 2010 and 2015 with an indication for gemcitabine and cisplatin were included. We divided these patients into three groups: (I) patients who received chemotherapy and met the criteria of the ABC-02 trial, (II) patients who received chemotherapy and did not meet these criteria and (III) patients who had an indication for chemotherapy, but received best supportive care without chemotherapy. Primary outcome was overall survival (OS) and secondary outcome was progression-free survival (PFS). Results: We collected data of 208 patients, of which 138 (66.3%) patients received first line chemotherapy with gemcitabine and cisplatin. Median OS of 69 patients in group I, 63 patients in group II and 65 patients in group III was 9.6 months (95%CI = 6.7–12.5), 9.5 months (95%CI = 7.7–11.3) and 7.6 months (95%CI = 5.0–10.2), respectively. Median PFS was 6.0 months (95%CI = 4.4–7.6) in group I and 5.1 months (95%CI = 3.7–6.5) in group II. Toxicity and number of dose reductions ( p = .974) were comparable between the two chemotherapy groups. Conclusion: First-line gemcitabine and cisplatin is an effective and safe treatment for patients with unresectable BTC who do not meet the eligibility criteria for the ABC-02 trial. Median OS, PFS and treatment side effects were comparable between the patients who received chemotherapy (group I vs. group II).